2022
DOI: 10.3389/fpsyg.2022.909266
|View full text |Cite
|
Sign up to set email alerts
|

The Nuance of Bilingualism as a Reserve Contributor: Conveying Research to the Broader Neuroscience Community

Abstract: The neurological notion of “reserve” arises from an individually observable dissociation between brain health and cognitive status. According to the cognitive reserve hypothesis, high-reserve individuals experience functional compensation for neural atrophy and, thus, are able to maintain relatively stable cognitive functioning with no or smaller-than-expected impairment. Several lifestyle factors such as regular physical exercise, adequate and balanced nutrition, and educational attainment have been widely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…58 Previous research revealed superior executive function and experience-dependent plasticity in older bilinguals, resulting in a greater cognitive reserve. 56 In our cohort, healthy older bilinguals with NCI had better general cognitive abilities compared to monolinguals, independent of the social determinants of health, such as age, sex, education, socioeconomic status, and occupation. Bilingual speakers scored better on attention, memory, fluency, language, and visuospatial subdomains of ACE-III compared to monolinguals.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…58 Previous research revealed superior executive function and experience-dependent plasticity in older bilinguals, resulting in a greater cognitive reserve. 56 In our cohort, healthy older bilinguals with NCI had better general cognitive abilities compared to monolinguals, independent of the social determinants of health, such as age, sex, education, socioeconomic status, and occupation. Bilingual speakers scored better on attention, memory, fluency, language, and visuospatial subdomains of ACE-III compared to monolinguals.…”
Section: Discussionmentioning
confidence: 57%
“…55 This is attributed to increased neuronal plasticity and better cognitive reserve resulting from practicing more than one language across the lifespan. 13,56 This is the first study investigating the impact of bilingualism on the prevalence of both dementia and MCI in a large population. We addressed the key methodological problems in earlier clinic and community studies to a greater extent in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the life-long experience of bilingualism has been suggested to be one of those challenging experiences that may bring about adaptations in cognition (Anderson, Mak, Keyvani Chahi & Bialystok, 2018;Bialystok, Craik, Klein & Viswanathan, 2004) and the brain (DeLuca, Rothman, Pliatsikas, 2020), and may lead to enhanced cognitive abilities in older adults (Bialystok et al, 2004;Samuel, Roehr-Brackin, Pak & Kim, 2018). It has even been suggested that the benefits of bilingualism in older age extend to increased cognitive flexibility and delay the onset of dementia symptoms (Bialystok, 2021;Craik, Bialystok & Freedman, 2010), both of which can be considered forms of cognitive reserve (Voits, DeLuca & Abutalebi, 2022a). It has been shown that both languages are constantly active, and competing, in the bilingual mind (Bialystok, Craik & Luk, 2012;Carlson & Meltzoff, 2008), a situation that requires bilinguals to inhibit the nontarget language and use the target language.…”
Section: Introductionmentioning
confidence: 99%